The role of upstream ULF waves in the generation of quasi-periodic ELF-VLF emissions - Morrison, K.; Freeman, M. P. (Annales Geophysicae, 1995)
Recent work suggests that the quasi-periodic (QP) modulation ~10–50 s of naturally occurring ELF-VLF radio emissions (~0.5–5 kHz) is produced by the compressional action of Pc3 magnetic pulsations on the source of the emissions. Whilst it is generally accepted that these magnetic pulsations have an exogenic source, it is not clear what the mechanism of their generation is. A study of QP emissions observed during 1988 at Halley, Antarctica, in conjunction with IMP-8 satellite solar wind data, shows that the occurrence and modulation frequency of the emissions are strongly dependent upon the direction and strength of the IMF, respectively. The observed relationships are very similar to those previously reported for Pc3 pulsations associated with upstream ion-cyclotron resonance, involving proton beams reflected at the bowshock. In comparing the observed QP modulation frequencies with upstream wave theory, agreement was found by considering wave excitation exclusively associated with a proton beam reflected from a position on the bowshock at which the shock normal is parallel to the ambient IMF direction. Other geometries were found to be either impropitious or uncertain. The work indicates the useful diagnostic role QP emissions could play in the study of compressional ULF waves in the upstream solar wind and in monitoring the IMF conditions responsible for their generation.